Optimal Parameters of Linear Dynamic Vibration Absorber for Reduction of Torsional Vibration - Vu, Xuan Truong; Khong, Doan Dien; Nguyen, Duy Chinh; Nguyen, Duc Toan (Old Journal, 2017)
This paper presents three analytical methods to determine optimal parameters of the passive mass-spring-disc dynamic vibration absorber (DVA), such as the ratio between natural frequency of DVA and shaft, damping ratio of DVA. The original model presented by Den Hartog, Luft and Warburton are solved and has shown in good agreement. Three analytical methods is then adopted for torsional shaft model. The simulation results indicate that the effectiveness in torsional vibration could be reduced. Finally, the optimal parameters of DVA were applied to decrease the shaft torsional vibration considering the vibration duration and stability criterion.